2019
DOI: 10.3390/su11184864
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Big Data Analytics on Company Performance in Supply Chain Management

Abstract: Big data analytics can add value and provide a new perspective by improving predictive analysis and modeling practices. This research is centered on supply-chain management and how big data analytics can help Romanian supply-chain companies assess their experience, strategies, and professional capabilities in successfully implementing big data analytics, as well as assessing the tools needed to achieve these goals, including the results of implementation and performance achievement based on them. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
2
41
0
6
Order By: Relevance
“…Many firms have invested heavily in big data with the aim of deriving important insights to gain sustainable competitive advantages. Recent literature has suggested that the innovation process need to create sustainable new capabilities such as big data analytics capability (BDAC) [1][2][3][4]. BDAC can help companies process the enormous amounts of available data to identify market opportunities, predict customer needs, and analyze customer purchase decisions [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many firms have invested heavily in big data with the aim of deriving important insights to gain sustainable competitive advantages. Recent literature has suggested that the innovation process need to create sustainable new capabilities such as big data analytics capability (BDAC) [1][2][3][4]. BDAC can help companies process the enormous amounts of available data to identify market opportunities, predict customer needs, and analyze customer purchase decisions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable organizational growth and performance is becoming a hot topic in the literature. The literature has suggested that sustainable organizations need to create sustainable new capabilities such as BDAC [1][2][3][4]. Prior studies have suggested that big data is an important sustainable resource for enterprises because they need new technologies to manage and analyze massive data and information [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McAfee and Brynjolfsson [1] proposed that big data can be characterized according to the 3V's of volume, variety, and velocity. Other scholars have added two additional V's of veracity and value [14,26]. In this study, we define big data as large, complex, and real-time data streams that require complex management, analysis, and processing techniques to extract valuable information [10].…”
Section: Big Datamentioning
confidence: 99%
“…Since the rise of the Internet and the digital economy, big data has become the most important technological change in business and academia, bringing considerable benefits to business, scientific research, public management, and other industries [1,2]. Many scholars have proposed that big data is one of the most important resources for firms to achieve sustainable development [26,28]. For example, big data can use production processes and supplier information to increase productivity, reduce cost losses, and achieve sustainable corporate development [5].…”
Section: Big Datamentioning
confidence: 99%